Transformasi Keberlanjutan Industri Penjaminan Kredit UMKM di Indonesia: Analisis PESTEL dengan Konteks Jamkrindo - Adrian Eka Darma Serang; Tiolina Evi (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the strategic environmental dynamics influencing the sustainability transformation of the MSME credit guarantee industry in Indonesia using the PESTEL framework. The guarantee industry was chosen because it plays a crucial role in expanding access to financing for MSMEs, while simultaneously facing increasingly complex pressures from policy, economic, social, technological, environmental, and legal perspectives. In this study, Jamkrindo is used as a contextual anchor to strengthen the empirical relevance of the analysis at the industry level. The research approach used is descriptive qualitative, based on literature review and document analysis, sourced from official regulations, institutional reports, statistical publications, and relevant corporate documents. The results show that political and legal factors are the main structural drivers through strengthening sustainable finance policies, strengthening the guarantee industry, and governance obligations, while economic and environmental factors influence portfolio quality and MSME business resilience. On the other hand, social and technological factors drive changes in stakeholder expectations, accelerated service digitalization, and the need for more adaptive risk assessments. Based on this synthesis, this study formulates a conceptual model that positions PESTEL pressures as drivers of strategic transformation in the guarantee industry, which then shapes ESG-based guarantee orientation and digital risk capabilities as the foundation for the sustainability of the MSME credit guarantee industry. The contribution of this research lies in extending the use of the PESTEL framework to the context of the guarantee industry's sustainability transformation, while also offering practical implications for Jamkrindo and the guarantee industry in building a more digital, inclusive, adaptive, and sustainable guarantee model. Keywords: PESTEL, MSME credit guarantee industry, sustainability transformation, ESG, digital risk capabilities, Jamkrindo